2012
DOI: 10.1021/ol300676w
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Activation of Stable Carboxylate Esters as Enolate Equivalents via N-Heterocyclic Carbene Catalysts

Abstract: The first N-Heterocyclic Carbene (NHC) mediated activation of stable carboxylate esters to generate enolate intermediates is disclosed. The catalytically generated arylacetic ester enolates undergo enantioselective reactions with α,β-unsaturated imines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
62
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 202 publications
(69 citation statements)
references
References 74 publications
4
62
0
3
Order By: Relevance
“…Although transesterification of unactivated esters has been reported through the use of achiral NHC catalysts [35][36][37][38] , only highly reactive vinyl esters were successful in the asymmetric versions 39 . Alternative nucleophile catalysis by NHC may occur for these reactions, as supported by recent work by Chi and co-workers 25,40,41 . Presumably, an acyl imidazolium cation intermediate is formed by the substitution of the vinyl alcohol with NHC, which in turn undergoes alcoholysis.…”
mentioning
confidence: 72%
“…Although transesterification of unactivated esters has been reported through the use of achiral NHC catalysts [35][36][37][38] , only highly reactive vinyl esters were successful in the asymmetric versions 39 . Alternative nucleophile catalysis by NHC may occur for these reactions, as supported by recent work by Chi and co-workers 25,40,41 . Presumably, an acyl imidazolium cation intermediate is formed by the substitution of the vinyl alcohol with NHC, which in turn undergoes alcoholysis.…”
mentioning
confidence: 72%
“…249 In stark contrast to the “forward” process that starts from an enal (or other α-functionalized aldehydes) and proceeds to the azolium enolate, the reverse process starts from a stable carboxylic ester bearing a good leaving group OR 2 (Scheme 222). The increased acidity of α C-H bonds of the saturated acylazolium intermediate would then lead to facile deprotonation and formation of the NHC-bound azolium enolate.…”
Section: Catalysis Involving Acylazolium Intermediatesmentioning
confidence: 99%
“…2a, while strong bases (such as NaH, KO t Bu, DBU) promote the formation of NHC-Cu complex B from the corresponding triazolium NHC pre-catalyst A and CuI, weak bases (such as TEA, DIEA, K 2 CO 3 ) led to little NHC-Cu complex after several hours. In our prior studies 27,[33][34][35] , it is known that weak bases such as DIEA or K 2 CO 3 are sufficient for the deprotonation of triazoliums to form the carbene catalyst. We therefore concluded that under 'weak' base conditions, there is a controllable kinetic/thermodynamic window that allows the carbene organocatalyst and Cu metal catalyst to co-exist with a meaningful level of concentrations.…”
Section: Resultsmentioning
confidence: 99%